Effect of age on total lipid and cholesterol of hen eggs - OLOYO, R A (The Indian Journal of Animal Sciences, 2014)
Duplicate groups each of 50O laying hens of 2 age group 5 (6 and 20 months old) were used to study the effecd of age on total lipid and cholesterol of eggs. The laying hens'were fed with a practical-type layer's ralion and were maintained under commercial egg pmduclion conditions. Average egg weight. yolk weight, tolal lipid (g) and total lipid (mg/g yolk) were significantly (P